The development of the macrogamete and oocyst wall in Eimeria maxima: immuno-light and electron microscopy. - Ferguson, D; Belli, S; Smith, N; Wallach, MG (2003)
We have identified, and followed the development of three macrogamete organelles involved in the formation of the oocyst wall of Eimeria maxima. The first were small lucent vacuoles that cross-reacted with antibodies to the apple domains of the Toxoplasma gondii microneme protein 4. They appeared early in development and were secreted during macrogamete maturation to form an outer veil and were termed veil forming bodies. The second were the wall forming bodies type 1, large, electron dense vacuoles that stained positively only with antibodies raised to an enriched preparation of the native forms of 56 (gam56), 82 (gam82) and 230 kDa (gam230) gametocyte antigens (termed anti-APGA). The third were the wall forming bodies type 2, which appeared before the wall forming bodies type 1 but remain enclosed within the rough endoplasmic reticulum and stained positively with antibodies raised to recombinant versions of gam56 (anti-gam56), gam82 (anti-gam82) and gam230 (anti-gam230) plus anti-APGA. At the initiation of oocyst wall formation, the anti-T. gondii microneme protein 4 positive outer veil detached from the surface. The outer layer of the oocyst wall was formed by the release of the contents of wall forming bodies type 1 at the surface to form an electron dense, anti-APGA positive layer. The wall forming bodies type 2 appeared, subsequently, to give rise to the electron lucent inner layer. Thus, oocyst wall formation in E. maxima represents a sequential release of the contents of the veil forming bodies, wall forming bodies types 1 and 2 and this may be controlled at the level of the rough endoplasmic reticulum/Golgi body.